Piper methysticum G. Forst (Piperaceae) in the central nervous system: phytochemistry, pharmacology and mechanism of action (Research, Society and Development, 2021)
Due to the continuous increase in incidents of diseases and disorders in the central nervous system as neurodegenerative disease, the growth of studies that seek to use herbal medicines has been observed, since these are more easily produced and more economically viable, in addition to having side effects to a lesser extent when compared to existing synthetic drugs. In this way, a wide variety of plants have been analyzed for their medicinal purposes and this review presents papers published from 1970 to 2021 that describe the chemical composition pharmacological activities and elucidates mechanisms of action in the central nervous system (CNS) of the species Piper methysticum (Kava-kava). The Kava-kava has a class of compounds that include tannins, alkaloids, benzoic acid, cinnamic acid, sugars, bornyl-cinnamate, stigmasterol, flavocavaines, mucilages, pyrones, tetrahydroiangonins, phytochemicals that are responsible for the pharmacological activities of this plant being thus more studied as anxiolytic, sedative and neuroprotection. Some action mechanisms that describe the performance of kava in the CNS were also addressed, Being the main ones related to blocking of sodium and calcium ion channels, modulation of the erythroid 2 pathway, to receptors such as γ-aminobutyric acid, glutamatergics, glycine and cannabinoid, as well as monoamine oxidase and acetylcholinesterase enzymes, in addition to neurotransmitters such as dopamine, serotonin and norepinephrine. Therefore, this study aims to open new paths for more in-depth pharmacological studies on Kava-kava, and its use in the central nervous system.